Nature as the Time Teller: Indigenous Mathematics of Time Calculation in Nepal (KMC Journal, 2022)
Mathematics of time calculation has remained an indigenous asset of different Nepali societies since time immemorial. In this work, we aimed to discover the indigenous ways of time calculation in Nepal in terms of time telling, estimation of time, estimation of seasons, and the way people transferred their indigenous knowledge to their further generations. Employing the phenomenological design of qualitative research, we used unstructured interviews as the tool for data collection. We interviewed seven people from different ethnic and cultural backgrounds using an interview guideline. We also used folk song called ‘Sita jee ko bhalaulo’ popular in district Baitadit of Sudur Paschim Province. We analyzed the information retrieved from those open-ended interviews. From the analysis, we concluded that people in Nepal used to observe the natural entities in their vicinity to estimate the time. While doing so, they used to observe the celestial bodies, shadows cast by the sun, and the visible changes in nature, as well as behaviours of animals. Likewise, they depended upon astrological calculations, and some provisions made by the state to inform people about time.